Kajian Literatur Kepuasan Pasien BPJS Kesehatan Terhadap Pelayanan di RSUD Kabupaten Tangerang dengan Fokus pada Komunikasi Partisipatif - Komariyah, Fadjrin Satriyani; Riyantini, Rini; ., Kusumajanti (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
Healthcare services for BPJS Kesehatan participants at RSUD Kabupaten Tangerang face various challenges, particularlyin communication between medical personnel and patients. The main issue lies in the low effectiveness of participatorycommunication, which results in patient dissatisfaction, miscommunication regarding service procedures, and limitedpatient involvement in medical decision-making. This situation is further exacerbated by the lack of communication training for healthcare staff, limited access to information for patients, and the complexity of BPJS regulations, which are often poorly understood by both parties. This study aims to examine the contribution of participatory communication to patient satisfaction among BPJS participants at RSUD Kabupaten Tangerang, identify the barriers to its implementation, and formulate strategies to enhance the quality of communication between medical staff and patients. The research method employed is library research, by collecting and reviewing various relevant academic literature on participatorycommunication, patient satisfaction, and the quality of healthcare services in hospital settings. The analytical techniqueused is descriptive qualitative analysis, intended to identify patterns, concepts, and relationships among the variablesdiscussed in the literature. The findings indicate that participatory communication significantly contributes to increasedpatient trust, satisfaction, and engagement. The main barriers identified include inadequate communication training, limited access to information, and complex healthcare regulations. Recommended strategies include communication training for medical staff, the development of a hospital management information system (SIMRS), enhanced patient education, and the establishment of an open communication culture to ensure continuous improvement in service quality.